Charles Wright (1811-1885) in Cuba as Revealed by His Letters - Morris K. Jacobson (Hello World!, 1974)
Among the best known collectors of Cuban land shells is the Connecticut-born botanist, Charles Wright. Ludwig Pfeiffer, who described and named most of the shells collected by Wright, credited him with discovering some 30 new species besides contributing such important ecological and distributional data. In addition, Rafael Arango frequently cites Wright as the source of much of the data which he published in his superb annotated catalog of Cuban shells (1878-1880).